ANALISA PEMILIHAN BARISTA DENGAN MENGGUNAKAN METODE TOPSIS (STUDI KASUS: MO COFFEE) - Hutasoit, Rahel Adelina; Solikhun, Solikhun; Wanto, Anjar (STMIK Budi Darma, 2018)
Along with the mushrooming of food & beverrage business in Pematangsiantar city, especially in this case is a coffee shop making a barista a bone of contention for business people in the world of food & beverrage business. This makes business people still feel confused and need information to decide to employ a barista that suits their wishes. The purpose of the study was to analyze the TOPSIS method in determining the selection of baristas with 4 alternatives, namely (A1) Alfian, (A2) Widharta, (A3) Sylviana, and (A3) Anisah. And has 6 assessment criteria, namely (C1) the ability to mix coffee, (C2) know coffee and its intricacies, (C3) taste ability, (C4) work experience, (C5) master the use of a set of coffee machine tools and accessories, and (C6) skill in making latte art. The data obtained will be processed using the TOPSIS method. The results of the study obtained (A3) Widharta with the preference weights (0,6126) as the first rank, followed by the second and third ranks (A2) Sylviana with preference weights (0,4980) and (A1) Disagree with preference weights (0.4597) . It is hoped that this research can help or provide input to Mo Coffee owner in choosing baristas to be employed.Keywords: Barista, TOPSIS, Decision Support System, Pematangsiantar, Assessment Factor, Mo Coffee